Pechiche (Vitex cymosa Berteo ex Speng), a Nontraditional Fruit from Ecuador, is a Dietary Source of Phenolic Acids and Nutrient Minerals, in Addition to Efficiently Counteracting the Oxidative-Induced Damage in Human Dermal Fibroblasts - Mabel Guevara; Luis A. Valdés-Silverio; María G. Granda-Albuja; Gabriel Iturralde; Tatiana Jaramillo-Vivanco; Francesca Giampieri; Celestino Santos-Buelga; Ana M. González-Paramás; Maurizio Battino; José M. Álvarez-Suarez (MDPI AG, 2020)
Pechiche fruits (Vitex cymosa Berteo ex Speng) from Ecuador were studied to determine their phenolic acid profile, nutrient minerals and capacity to protect primary human dermal fibroblasts (HDFa) against oxidative-induced damage. Up to five phenolic acids were identified, with homovanillic acid as the main one. Vitamin C, β-carotene and lutein were also determined. Phosphorus and potassium were the main macrominerals, while iron was the principal micromineral. HDFa were preincubated with a crude pechiche extract (PCext) and then subjected to oxidative stress. The activity of five antioxidant enzymes, intracellular reactive oxygen species (ROS) and ATP levels and lipid peroxidation and protein oxidation were used as markers of oxidative damage. Preincubation with PCext for 24 h allowed for the significant reduction of intracellular ROS levels, improved the intracellular ATP levels and protected lipids and proteins against oxidative damage (p < 0.05). Additionally, preincubation with PCext was also able to significantly (p < 0.05) improve the activity of the antioxidant enzymes catalase, superoxide dismutase, glutathione peroxidase, glutathione reductase and glutathione transferase, compared to the stressed group without pretreatment. The results obtained in this study suggest the potential of pechiche as a source of bioactive compounds, as well as its beneficial effect against oxidative stress.